Triple Helix Model to Optimize Performance in the Coal Contractor Company PT. XYZ (Human Resources Management Review) - Septiana, Hanna; Mz, Masydzulhak Djamil (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
Knowing and analyzing the Triple Helix model can optimize the performance of the coal contractor company PT. XYZ. The population of this research is all employees at PT. XYZ. Data collection used survey and questionnaire interview methods. The data analysis technique uses AHP (Analytical Hierarchy Process) with six criteria built on existing theories, namely: Ability and Expertise, Work Design, Motivation, Leadership, Organizational Culture, and Commitment. The results obtained are that the answers from respondents have met the consistency requirements and the model built has been proven to be good in terms of sensitivity or stability. The Triple Helix Model in this research shows that it can improve the performance of PT. XYZ